Correlation Between Language Learning Strategies and Students Motivation in Learning English - Novi Rizki Amelia; Silvi Sultonah; Amalia Syarifah Gusdary, (Journal of Applied Linguistics (ALTICS), 2024)
This study focuses to find out the correlation between language learning strategies ( LLS) and Students’ Motivation in English learning at Eighth Grade of Universitas Perjuangan Tasikmalaya. This study used a Correlation method. The Sample of this study are English students from class of 2020, 2021 and 2022 who were randomly selected using simple random sampling. The true sample taken in this study was 29 English students in the class of 2021. The instruments used were two questionnaires regarding Language learning Strategies (LLS) and Students Motivation. The results of this study will prove whether there is a correlation between students' learning strategies on their motivation to learn English. Based on what researchers' found after calculating the value by using SPSS, the significance value is 0,705, which is less than 0,05. It means the two variables are not correlated. While the value of Pearson correlation is -0,73 which indicates that there is no correlation between the two variables. Keywords: Correlation, Language learning strategies, students motivation, English Learning